Lyapunov-based Nonlinear Vibration Control of an Underactuated Aircraft Wing Model - Al-Shuka, Hayder F.N.; Corves, Burkhard (Recent Research Reviews Journal, 2024)
This research presents a coupling nonlinear vibration control strategy for an underactuated wing model, characterized as a rigid link with translational and rotational springs that signify its structural stiffness. Stabilized by a single flap control surface, the system poses a complex control challenge. The control law design involves two steps: Step one employs coordinate transformation to create an equivalent simplified dynamic system with a new virtual control input through partial feedback linearization. Step two formulates a control law for this virtual input based on Lyapunov’s theory, ensuring stability. Unlike conventional feedback linearization, this approach does not require assessing the system's internal stability. Moreover, the control law includes coupled terms related to the generalized coordinates of the target system with stabilized motion. MATLAB/SIMULINK simulations confirmed the effectiveness of the control structure in attenuating wing oscillations, despite the controller being non-adaptive and operating under assumed known wing model parameters.
Keywords: Nonlinear Coupling Control; Lyapunov Theory; Underactuated Wing; Partial Feedback Linearization